Geographic, taxonomic and metric gaps in biodiversity research limit evidence‐based conservation in agricultural landscapes: An umbrella review - Bonfanti, Jonathan; Langridge, Joseph; Avadí, A.; Casajus, N.; Chaudhary, A.; Damour, G.; Estrada-Carmona, Natalia; Jones, Sarah K.; Makowski, D.; Mitchell, M.; Seppelt, R.; Beillouin, Damien (Wiley, 2025)
Agriculture is fundamentally dependent on biodiversity, yet unsustainable management practices increasingly threaten various organisms and ecosystem services. Confronting the global crisis of biodiversity loss requires a thorough understanding of the gaps, clusters and biases in existing knowledge across various management practices, spatial scales, and taxonomic groups. We undertook a comprehensive literature review, synthesising secondary data from 200 meta‐analyses on agricultural management impacts on biodiversity in croplands. Our systematic map covers 1885 comparisons (mean effect sizes), from over 9000 primary studies. In the latter, seven high‐income countries prevail (notably the USA, China and Brazil), with particular focus on fertiliser use, phytosanitary interventions and crop diversification. This emphasis on individual practices overshadows research at the farm and landscape levels. In secondary evidence, arthropods and microorganisms are most frequently studied, while annelids, vertebrates and plants are less represented. Evidence predominantly stems from averaged abundance data, revealing substantial gaps in studies on functional and phylogenetic diversity. Our findings highlight the need to analyse combinations of multiple practices to accurately reflect real‐world farming contexts, and covering a wider range of taxa, biodiversity metrics and spatial levels, to enable evidence‐based conservation strategies in agriculture. Given the uneven evidence on agricultural impacts, caution is required when applying meta‐analytical findings to public policies and global assessments.